Report on CURENT ISSUES OF OPHTHALMOLOGY, a Sientific and Practical Conference of Ophthalmologists of Chernivtsi, Ivano-Frankivsk, Ternopil, Khmelnitsk Regions of Ukraine (Ukrainian Journal of Ophthalmology, 2026)
CURENT ISSUES OF OPHTHALMOLOGY, a Sientific and Practical Conference of Ophthalmologists of Chernivtsi, Ivano-Frankivsk, Ternopil, Khmelnitsk Regions of Ukraine was held in Chernivtsi on the 20th -21st of September 2017. This event was held by Filatov Eye Disease and Tissue Therapy Institute, NAMS of Ukraine together with Bukovinian State Medical University and supported by Chernivtsi Region State Administration and City Council, the Department of Health of Chernivtsi Regional State Administration in accordance with the plan of organizational measures of the Ministry of Health of Ukraine, NAMS of Ukraine and the Register of Congresses, Symposia and Scientific-Practical Conferences to be held in 2017.